The productive efficiency of community health service stations in China: Taking Shandong province as a case. (6th January 2022) - Qiu, Leijie; Yang, Linsheng; Li, Hairong; Wang, Li
Abstract: The present study evaluated the efficiencies of community health service (CHS) stations based on a survey of 1246 CHS stations, covering nine subcategories in 16 cities in Shandong province. Data envelopment analysis (DEA) was applied to investigate the overall efficiency, the technical and the scale efficiency of community health care resources. The results are, the overall efficiency was 9.47%, and the overall efficiency was generally higher in the central‐west region than in the east. There were 23.27% of CHS stations showing technically efficient. The technical efficiency was higher in the east (31.11%) relative to the central‐west (19.72%), and 72.71% of CHS stations had a technical efficiency higher than the regional average efficiency. The scale efficiency was 9.31% for CHS stations in Shandong province, being the decisive factor for overall efficiency, and 68.96% of CHS stations showed a scale efficiency above the regional average. Stations held by enterprises and universities, and extended by tertiary hospitals had lower efficiencies than other types of CHS stations. In conclusion, the CHS stations had low efficiencies in general, and scale inefficiencies were the main cause. Related suggestions to improve the efficiency are provided accordingly. Highlights: The overall efficiency of community health service (CHS) stations in Shandong province was generally low, with efficiency higher in the central‐west than in the east. Scale efficiency is the main factor impacting the overall efficiency for CHS stations in Shandong province. Stations held by enterprises and universities, and extended by tertiary hospitals had lower efficiencies than other types of CHS stations.